Implementasi Model Pembelajaran Cooperative Learning Tipe STAD untuk Meningkatkan Hasil Belajar Siswa dalam Pembelajaran PAI dan Budi Pekerti di SMP Namira Kota Probolinggo - Abdul Hamid; Dimas Adji Pangestu; Devy Habibi Muhammad (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
Efforts to improve the Learning Outcomes of Class VIII Junior High School Students in Islamic Religious Education Subjects with the STAD Type Cooperative Learning Model at Namira Middle School, Probolinggo City, for the 2022/2023 Academic Year. This research is a classroom action research that aims to improve student learning outcomes of SMP Namira City Probolinggo class VIII-B with the STAD Type Cooperative Learning learning model. The subjects of this study were students of class VIII-B SMP Namira Probolinggo City as many as 20 students. The information collection tool used is in the form of observation sheets and ordinary multiple preference objective tests, based on the results of observations in cycle I and cycle II activities, there is an increase in student learning outcomes. Universally obtained 75% of students in the first cycle and 100% in the second cycle. This increase in learning outcomes took place because each student discussed the division of his group members into expert groups based on the teacher's direction, as well as in the group from which students were eager to present the results of the discussion. Next, it was found that the increase in learning outcomes that appeared in the gain index criteria for each student were 5 incomplete, 12 medium students and 3 high students above 90 in the first cycle, 20 students completed and most of them increased in the second cycle.